(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
Ecology-coenotic features of the Epipactis helleborine population in spontaneous (transformed and regenerative) forest phytocenoses with predominance of Carpinus betulus, Acer platanoides and Quercus robur stands in «Lysa Hora» (Kyiv) tract were studied. Previously, several finds of this species were known in the regional landscape park «Lysa Hora», which allowed a comparative chorological analysis of Epipactis helleborine and the probability of dissemination (migration) in time and space due to natural (afforestation, change of shading, succession processes, species competition, soil erosion), anthropogenic (trampling along roads, formation of lighted areas, protected area) impacts. The aboriginal population of autochthonous origin is quite large in area ( 1500×500 m) and formed about 1000 individuals of all ontogenetic stages, which are located mainly in the central part of the tract «Lysa Hora» and is probably one of the largest and most stable (homeostasis) populations in Ukraine. The current state of the population of Epipactis helleborine was shown, its syntaxonomic status was determined and the hypothesis of prospects for further development was substantiated. The regularities of the ontogenesis of Epipactis helleborine in urban growth conditions in an orographically disjunctive, fragmented area have been elucidated. Relatively high resistance (vitality) to recreational impact, trampling, shading, as well as satisfactory competitiveness in forest sinuses, resistance to disease and arid weather and climatic conditions was detected. Forest phytocenoses with Epipactis helleborine belong to the class Carpino-Fagetea sylvaticae, order Carpinetalia betuli, alliance Carpinion betuli, association Galeobdolo lutei-Carpinetum.